The Influence Of Facilities And Infrastructure Management On The Effectiveness Of The Teaching And Learning Process At Superior High School Aceh Besar - Erlina Devayani; Bahrun Bahrun; Khairuddin Khairuddin (JETL (Journal of Education, Teaching and Learning), 2024)
Facilities and infrastructure are resources that are really needed in the school environment to support the smooth teaching and learning process. The role of the school principal is very important in managing facilities and infrastructure, including assistance from educational staff, facilities and infrastructure and cooperation with the school community in maintaining school facilities and infrastructure so that they remain strong and last a long time. Management of facilities and infrastructure greatly influences the teaching and learning process so that there are no obstacles such as damage and loss of facilities/equipment that have been provided. The aim of this research is to determine the influence of facilities and infrastructure management on the effectiveness of the teaching and learning process at SMAN Unggul Aceh Besar. This study uses a quantitative approach. Data collection techniques use observation, interviews, documentation and questionnaires. The data analysis technique uses a qualitative and quantitative approach using the T and N-Gain tests. Based on research findings, there areThe significant influence of facilities and infrastructure management on the teaching and learning process as seen based on the T test shows very high significance (0.000) and the N-Gain test shows that the N-Gain value is 0.71 or around 71%. Therefore, management of infrastructure in the teaching and learning process is effective.